Pengaruh Edukasi terhadap Self Eficacy Lansia dalam Mengatasi Nyeri Sendi dan Meningkatkan Mobilisasi - Pudjiati Pudjiati; Rosidawati Rosidawati; Mia Fatma Ekasari (Jurnal Keperawatan, 2018)
Education is an effort to give informations which is expected to improve client’s self efficacy that is able to change client’s behavior to relieve joint pain faster. Furthermore, education that will be given to relieve joint pain and mobilization is warm compress and gymnastic for elderly. This research uses quasi-experiment with control group design as a method. This research intervenes gymnastic and warm compress for elderly. The sample of this research itself is the elderly who have mild to moderate joint pain through strategic sampling, purposive sampling and the sample size will use two different means test formula (Lemeshow, Holmer, Klar & L Wanga, 2009). The sample in this research consists of two group, i.e., intervention group which has 40 people and control group which has 40 people. This research uses self-efficacy questionnaire for the elderly in relieving pain and improving mobilization. The result of this research uses bivariate hypothesis test that shows education of gymnastic for elderly and warm compress is more to affect the self-efficacy of the pain and mobilization.